PENGARUH KOMPENSASI FINANSIAL, PROMOSI JABATAN DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PARIGATA RESORT AND SPA SANUR - BALI - Setiawan, I Wayan Oky; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2013)
The purpose of this paper is to determine the impact of financial compensation, post promotion and physical work environment simultaneously and partially to employee work satisfaction as well as to identify the most dominant influential variable to employee work satisfaction in Parigata Resort and Spa Sanur – Bali. Analysis is using multiple linear regressions. The result is identified that variable financial compensation, post promotion and physical work environment simultaneously impact the employee work satisfaction in Parigata Resort and Spa Sanur – Bali with contribution 82%. Variable financial compensation, post promotion and physical work environment are also impact partially and positively to the employee work satisfaction in Parigata Resort and Spa Sanur – Bali with the variable financial compensation as the most dominant influential variable to employee work satisfaction.   Keywords : financial compensation , post promotion, physical work environment, employee work satisfaction